Danube Triangle: Romania-Ukraine-Moldova: Problems and Prospects of Interstate Cooperation - D. G. Dragan (Проблемы постсоветского пространства, 2020)
This article analyses the foreign policy of Romania, Ukraine, and Moldova as well as the evolution of institutional establishment in the region of the Danube. Research shows that the Danube Commission is the main platform for policy coordination but at the same time the interstate dialogue on regional problems is maintained at other levels, by implementing the EU Strategy for the Danube Region and establishing Euroregions for cross-border cooperation. Considering this, it is necessary to specify the concrete spheres of cooperation between the countries: the development of transport, infrastructure, communication, as well as cooperation in environmental protection and the humanitarian field.The article draws attention to certain factors that determine the moderate character of the relations between the countries of the Triangle “Romania–Ukraine–Moldova”. First and foremost the problems of bilateral cooperation, second — the existing external and internal conditions.In this regard, the author specifies certain risks that the countries of the region face. It is difficult to resolve disputes between the states because of their different statuses. It is also worth noting that ignoring strategic risks can also lead to transport isolation.